Rosas: Kulay at Kilusan (Pink: Color and Movement) - Santos, Mark Joseph (Social Sciences and Development Review, 2023)
The history of pink as a color is complex. Different groups — such as feminists, breast cancer patients, the LGBTQ+ community, and socialists — have given various interpretations of it before it finally entered the Philippines. In the context of the 2022 presidential election, pink transformed into a movement centered on the candidacy of Leni Robredo. This movement can be labeled the “Color Pink Movement.” Aside from historicizing the politics of the color pink in both global and national contexts, this essay aims to describe the Color Pink Movement by applying the concept of maganda (beauty), which was first comprehensively conceptualized by the theologian Jose de Mesa. Its kagandahang panlabas (outer beauty)—expressed through the arts (poetry, comics, songs, dance, painting, theater, toys, and games)—and its volunteerism are aesthetic manifestations of the ethics of the Color Pink Movement: the kagandahang panloob (inner beauty) of a movement that believes love is the more radical act.
Keywords: pink; Color Pink Movement; Leni Robredo; beauty